UPAYA PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN METODE SNOWBALL THROWING PADA MATA PELAJARAN MATEMATIKA KELAS III - Adi Saputra; Masrutotul Mahmudah; Nur Laili (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This classroom action research aimed to improve the mathematics learning outcomes of third-grade students at MI Ma’arif NU 06 Karyamukti on the topic of plane geometry through the implementation of the Snowball Throwing cooperative learning model. The background of this study was the low student learning outcomes, as indicated by the pre-cycle mastery percentage of 41.18%. The research was conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection based on Kurt Lewin’s model. The research subjects consisted of 17 students. Data collection techniques included learning outcome tests and observation sheets of student activities during the learning process. The results showed an improvement in learning mastery in each cycle, from 41.18% in the pre-cycle, increasing to 58.82% in Cycle I, and reaching 82.35% in Cycle II. This improvement indicates that the implementation of the Snowball Throwing learning model was able to enhance students’ activeness, participation, and understanding of mathematics material. Therefore, the Snowball Throwing learning model is effective in improving mathematics learning outcomes for elementary school students. ABSTRAK Penelitian tindakan kelas ini bertujuan untuk meningkatkan hasil belajar matematika siswa kelas III MI Ma’arif NU 06 Karyamukti pada materi bangun datar melalui penerapan model pembelajaran kooperatif tipe Snowball Throwing. Latar belakang penelitian ini adalah rendahnya hasil belajar siswa yang ditunjukkan oleh persentase ketuntasan pra-siklus sebesar 41,18%. Penelitian dilaksanakan dalam dua siklus yang masing-masing meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi sesuai model Kurt Lewin. Subjek penelitian berjumlah 17 siswa. Teknik pengumpulan data menggunakan tes hasil belajar dan lembar observasi aktivitas siswa selama proses pembelajaran. Hasil penelitian menunjukkan adanya peningkatan ketuntasan belajar pada setiap siklus, yaitu dari 41,18% pada pra-siklus, meningkat menjadi 58,82% pada siklus I, dan mencapai 82,35% pada siklus II. Peningkatan tersebut menunjukkan bahwa penerapan model Snowball Throwing dalam pembelajaran mampu meningkatkan keaktifan, partisipasi, serta pemahaman siswa terhadap materi matematika. Dengan demikian, model pembelajaran Snowball Throwing efektif digunakan untuk meningkatkan hasil belajar matematika pada siswa sekolah dasar.